2020
DOI: 10.1038/s42003-020-01454-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum sexual parasites regulate infected erythrocyte permeability

Abstract: To ensure the transport of nutrients necessary for their survival, Plasmodium falciparum parasites increase erythrocyte permeability to diverse solutes. These new permeation pathways (NPPs) have been extensively characterized in the pathogenic asexual parasite stages, however the existence of NPPs has never been investigated in gametocytes, the sexual stages responsible for transmission to mosquitoes. Here, we show that NPPs are still active in erythrocytes infected with immature gametocytes and that this acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…chromatin organization and protein transport) or with unknown functions 8,27 . In addition, cAMP/PfPKA-dependent signalling has been implicated in the regulation of ion channel conductance and new permeability pathways (NPP) in asexual blood stage parasites 28 and gametocytes 29 as shown through the use of pharmacological approaches (PKA/PDE inhibitors, exogenous 8-Bromo-cAMP) and transgenic cell lines (deletion of PfPDEδ, overexpression of PfPKAr) 28,29 . Similar experiments identified a putative role for cAMP/PfPKA-dependent signalling in regulating gametocyte-infected erythrocyte deformability 30 .…”
Section: Introductionmentioning
confidence: 99%
“…chromatin organization and protein transport) or with unknown functions 8,27 . In addition, cAMP/PfPKA-dependent signalling has been implicated in the regulation of ion channel conductance and new permeability pathways (NPP) in asexual blood stage parasites 28 and gametocytes 29 as shown through the use of pharmacological approaches (PKA/PDE inhibitors, exogenous 8-Bromo-cAMP) and transgenic cell lines (deletion of PfPDEδ, overexpression of PfPKAr) 28,29 . Similar experiments identified a putative role for cAMP/PfPKA-dependent signalling in regulating gametocyte-infected erythrocyte deformability 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the different strategies evolved by P. falciparum parasites to persist for such a long time in the peripheral blood, gametocytes modify the mechanical properties of their erythrocyte host. As observed in mature asexual stages [4][5][6], immature gametocytes increase the stiffness and the permeability of their host cell by exporting proteins to the erythrocyte membrane [7,8]. The increase in stiffness is linked to both the interaction of the parasite proteins STEVOR with one or several erythrocyte membrane skeleton proteins composing the ankyrin complex [9,10] and to the remodelling of lateral and vertical interactions within the erythrocyte skeleton [11].…”
mentioning
confidence: 96%
“…The increase in permeability is due to the activation of the new permeability pathways (NPPs) in which the RhopH proteins play an important role [7,12]. However, unlike in asexual stages, these changes in erythrocyte membrane mechanical properties are reversible in sexual stages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unknown whether XA can diffuse through the red blood cell and the parasitophorous vacuole membranes. It was recently shown that P. falciparum gametocytes regulate infected erythrocyte permeability via the new permeability pathway (Bouyer et al, 2020). However, this activity declines along gametocyte maturation and it is also uncertain whether XA could further traverse the parasite plasma membrane to reach GCα.…”
Section: Sensing the Environment By Multipass Membrane Enzymes Regulating Cgmp Homeostasismentioning
confidence: 99%